Identifying Risk Factors for Complications in Gynecologic Laparoscopic Surgery: A Retrospective Study - Aiwen Le; Yahong Xu; Jinyuan Cui (IMR Press, 2023)
Background: This study aimed to investigate the risk factors associated with complications following gynecologic laparoscopic surgery. Methods: A retrospective analysis was conducted on patients who underwent gynecologic laparoscopic surgery at Huazhong University of Science and Technology Union Shenzhen Hospital between January 2005 and October 2021. The study population was divided into four groups based on the type of surgery: adnexal surgery, myomectomy/other uterine lesions, laparoscopically assisted vaginal hysterectomy (LAVH)/total laparoscopic hysterectomy (TLH), and surgery for malignancy. The rates of major and minor complications were compared and factors influencing the occurrence of complications were analyzed. Results: A total of 15,308 patients were included in this study. The rates of major and minor complications were 0.51% (78/15,308) and 4.64% (711/15,308), respectively. Multivariate logistic regression analysis revealed that older age (31-60 years-old vs. 18-30 years-old: adjusted odds ratio (aOR): 2.88, 95% confidence interval (CI): 1.89-7.88; >60 years-old vs. 18-30 years-old: aOR: 2.92, 95% CI: 1.67-5.65), prior abdominal surgery (aOR: 3.58, 95% CI: 1.38-6.54), obesity (aOR: 2.52, 95% CI: 1.39-7.28) and surgical complexity (myomectomy/surgery for other uterine lesions vs. adnexal surgery: aOR: 1.56, 95% CI: 1.23-3.45; LAVH/TLH vs. adnexal surgery: aOR: 3.87, 95% CI: 1.39-8.23; surgery for malignancy vs. adnexal surgery: aOR: 7.62, 95% CI: 3.61-13.63) were associated with major complications. Conclusion: The rates of major and minor complications following gynecologic laparoscopic surgery were found to be low. Age, surgical complexity, previous abdominal surgery, and obesity are identified as risk factors for major complications.